Energy transition in municipalities – a model for sustainable renewable energy management - Aneva, Sara (Journal of energy technology, 2025)
This study explores optimal strategies for utilizing the electricity generated from already installed PV systems at the local level, aiming to reduce electricity costs and increase revenues through the sale of surplus electricity. Two scenarios are analyzed: (1) individual consumption of the generated electricity within each building and the sale of surplus electricity at the time of production, and (2) collective energy management through a municipal energy enterprise, where surplus electricity is distributed among buildings, and the remaining surplus is sold on the free market. By analyzing existing research and case studies, the study seeks to determine which strategy is more efficient regarding energy efficiency and financial viability, and to propose a model for the collective management of electricity generated from PV systems at the municipal level.
Keywords: electricity cost reduction; energy management; komunalno energetsko podjetje; municipal energy enterprise; presežki električne energije; PV sistemi; PV systems; surplus electricity; upravljanje z energijo; zniževanje stroškov električne energije